Airway management in head and neck cancer patients undergoing microvascular free tissue transfer: delayed extubation as an alternative to routine tracheotomy (Swiss Medical Weekly, 2014)
QUESTIONS UNDER STUDY: The aim of this study was to evaluate two practices of airway management in patients undergoing head and neck cancer (HNC) resection and microvascular free tissue transfer (MFTT), and to assess the advantages and disadvantages of the two approaches. METHODS:Patients undergoing a delayed extubation approach (NO-TRACH group) and patients undergoing primary tracheotomy (PRIM-TRACH group) were retrospectively evaluated in terms of perioperative and postoperative outcome measures. RESULTS:Not performing routine tracheotomy was safe and no perioperative airway complications occurred. NO-TRACH patients were extubated after 1.1 ± 0.9 days (mean ± standard deviation) and secondary tracheotomy was necessary in three patients (13%). NO-TRACH patients revealed decreased duration of surgery (p